Membrane Remodeling by Arc/Arg3.1 - Hedde, Per Niklas; Malacrida, Leonel; Barylko, Barbara; Binns, Derk D.; Albanesi, Joseph P.; Jameson, David M. (Frontiers in Molecular Biosciences, 2021)
The activity-regulated cytoskeletal-associated protein (Arc, also known as Arg3.1) is an immediate early gene product induced by activity/experience and required for multiple modes of synaptic plasticity. Both long-term potentiation (LTP) and long-term depression (LTD) are impaired upon Arc deletion, as well as the ability to form long-term spatial, taste and fear memories. The best-characterized function of Arc is enhancement of the endocytic internalization of AMPA receptors (AMPARs) in dendritic spines. Solution of the crystal structure of a C-terminal segment of Arc revealed a striking similarity to the capsid domain of HIV Gag. Moreover, Arc assembles into viral capsid-like structures that enclose Arc mRNA, are released into the extracellular space, and are internalized by neighboring cells. Thus, Arc is unique in promoting plasma membrane budding both into and out of the cell. In this report we study the interaction of Arc with membranes using Giant Unilamellar Vesicles, by monitoring the overall effect of the protein on the morphology of the vesicles. The physical states of the membranes were also elucidated using the fluorescent probe LAURDAN. Arc was also covalently labeled with Alexa probes to visualize its interaction with GUVs.